Potensi Pati Ganyong (Canna edulis) dan Pati Singkong dalam Produksi Asam Levulinat - Angela M (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Levulinic acid (LA) is a platform chemical which isproduced using petroleum-derived raw material thatis having crisis these days. Therefore it is needed tofind an alternativee raw material. One of them is a renewable tuber which is abundantly in Indonesia. The goal ofthis research is to study the potentiality of starch derived from canna edulis and cassava in producing LA and the effect of reaction conditions i.e. the concentration of acid catalyst and the reaction temperature on the yield of LA. This research was performed in a pressurized stirred reactor for 60 minutes. The variables usedare the concentration of sulfuric acid catalyst (5%, 10%, 15%-wt.) and the reaction temperature (150oC and 180oC). Ratio between starch and sulfuric acid is 1:10 (wt./v). The carbohydrate content in starch was analyzed by Anthrone method. Whereas, the product was analyzed by High Performance Liquid Chromatography (HPLC). The result of this study shows that the reaction temperature and the carbohydrate content in starch determine the yield of LA. However, the concentration of sulfuric acid affects the type of starch instead ofthe yield of LA. The further research will study about the effect of starch characteristic into the yield of LA.